Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

I can't prove this trigonometric identity. Can somebody help me?

Attachment image

2 Answers

Relevance
  • 4 years ago
    Favorite Answer

    Hello,

    let's work on the left side:

    [1 /(sin²a + cos²a + tg²a)] - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    let's apply (in the first denominator) the fundamental identity sin²a + cos²a = 1:

    {1 /[(sin²a + cos²a) + tg²a]} - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    [1 /(1 + tg²a)] - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    let's express the tangent in terms of sine and cosine:

    {1 /[1 + (sin a /cos a)²]} - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    {1 /[1 + (sin²a /cos²a)]} - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    (letting cos²a be the common denominator)

    {1 /[(cos²a + sin²a) /cos²a]} - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    let's apply the fundamental identity cos²a + sin²a = 1:

    [1 /(1 /cos²a)] - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    cos²a - {sin²(90°+ a) + [cos(90°+ a) /sin a]} =

    let's consider both arguments (90°+ a) as [90° - (- a)]:

    cos²a - { {sin[90° - (- a)]}² + {cos[90° - (- a)] /sin a} } =

    let's apply the co-function identity sin(90° - θ) = cosθ (being of course in this case θ = - a)

    cos²a - {[cos(- a)]² + {cos[90° - (- a)] /sin a} } =

    similarly, let's apply the co-function identity cos(90° - θ) = sinθ (being of course in this case θ = - a)

    cos²a - {[cos(- a)]² + [sin(- a) /sin a]} =

    let's apply the trig identity cos(- a) = cos a:

    cos²a - {(cos a)² + [sin(- a) /sin a]} =

    similarly, let's apply the trig identity sin(- a) = - sin a:

    cos²a - {cos²a + [(- sin a) /sin a]} =

    cos²a - [cos²a - (sin a /sin a)] =

    (simplifying)

    cos²a - (cos²a - 1) =

    cos²a - cos²a + 1 =

    1

    (Q.E.D.)

    I hope it's helpful

  • Como
    Lv 7
    4 years ago

    sin (90 + a) = cos a

    cos (90 + a) = - sin a

    1 + tan²a = sec²a

    thus

    1 / sec²a - [ cos²a - 1 ] = cos²a - cos²a + 1 = 1

Still have questions? Get your answers by asking now.